Association of ultraprocessed foods consumption and cognitive function among children aged 4–7 years: a cross-sectional data analysis - Liu, Shun; Mo, Caimei; Lei, Lidi; Lv, Fangfang; Li, Jinxiu; Xu, Xuemei; Lu, Peini; Wei, Gangjie; Huang, Xuanqian; Zeng, Xiaoyun; Qiu, Xiaoqiang (Frontiers in Nutrition, 2023)
1) Background: Sugar-sweetened beverage (SSB) consumption has shown associations with cognitive function in preschool children, but effects of other ultraprocessed foods consumption are rarely discussed in China. This study aimed to investigate the relationship between ultraprocessed food consumption and cognitive function among preschool children in China. (2) Methods: A total of 325 children aged 4-7 years were included from Guangxi Zhuang Birth Cohort in Guangxi Zhuang AutonomousRegion, China. Face-to-face interviews with parents using the Food Frequency Questionnaire (FFQ) was conducted to investigate the status of seven ultraprocessed foods consumption (i.e. chocolate, biscuits, candy, fast-food, ice cream, SSBs, and sweet bakery products). The mandarin-language version of the Wechsler Preschool and Primary Scale of Intelligence (WPPSI, Fourth Edition) was applied to assess the cognitive function of children. Multiple linear and logistic regression models were used to assess the associations between ultraprocessed food consumption and the full-scale intelligence quotient (FSIQ) and different domains and risk of cognitive deficit, respectively. (3) Results: We found that frequent consumption of candy (β = -3.34, 95%CI: -5.62~-1.06; p = 0.004) and sweet bakery products (β = -2.77, 95%CI: -5.58~0.04; p = 0.054) were significant associated with decreased FSIQ scores in the linear regression models. However, only frequent consumption of candy was statistically significantly associated with an increased risk of cognitive deficit (OR = 2.05, 95% CI: 1.11~3.79; p = 0.023) in the logistic regression models. For the different domains, we found frequent consumption of candy (β = -3.85, 95%CI: -6.28~-1.43; p = 0.002) and sweet bakery products (β = -3.48, 95%CI: -6.47~-0.49; p = 0.023) was also significantly associated with lower Verbal Comprehension Index (VCI). When combining the seven ultraprocessed foods, we found children who frequently consumed more than two kinds of ultraprocessed foods had a significant decrease of VCI scores (β = -2.66; 95%CI: -5.12~-0.19; p = 0.035) too. (4) Conclusions: Our results suggested that frequent consumption of individual (candy and sweet bakery products) and multiple ultraprocessed foods may decrease VCI scores and thereby impact cognitive function in children aged 4-7 years.